2018
DOI: 10.1186/s12936-018-2235-3
|View full text |Cite
|
Sign up to set email alerts
|

Climatic fluctuations and malaria transmission dynamics, prior to elimination, in Guna Yala, República de Panamá

Abstract: BackgroundMalaria has historically been entrenched in indigenous populations of the República de Panamá. This scenario occurs despite the fact that successful methods for malaria elimination were developed during the creation of the Panamá Canal. Today, most malaria cases in the República de Panamá affect the Gunas, an indigenous group, which mainly live in autonomous regions of eastern Panamá. Over recent decades several malaria outbreaks have affected the Gunas, and one hypothesis is that such outbreaks coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 71 publications
3
31
0
3
Order By: Relevance
“…Coherence and wavelet phase analysis shows that local environmental conditions play an important role in the vector's seasonal cycle 41 . Consistent with the findings by Hurtado et al 42 , the relations between the variables indicated a strong annual pattern, in addition to significant coherences on the scale of variability less than one year and on the biennial scale. According to Chowell et al 43 , a strong annual pattern can be followed by biennial cycles, but differing by region and by type of malaria.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Coherence and wavelet phase analysis shows that local environmental conditions play an important role in the vector's seasonal cycle 41 . Consistent with the findings by Hurtado et al 42 , the relations between the variables indicated a strong annual pattern, in addition to significant coherences on the scale of variability less than one year and on the biennial scale. According to Chowell et al 43 , a strong annual pattern can be followed by biennial cycles, but differing by region and by type of malaria.…”
Section: Discussionsupporting
confidence: 89%
“…The malaria vector is susceptible to meteorological changes, which directly affect the mosquito's life cycle 10 . Information on the potential impact of climatic factors on malaria incidence can be useful for orienting disease prevention programs, aimed at the ultimate elimination of the disease 42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, evidence about ENSO impacts on malaria transmission dynamics in Panamá was added. Previously, it has been described that malaria transmission in the main endemic regions of Panamá, Comarca Guna Yala and Comarca Guna de Madugandi, peaks follow ENSO oscillations [10,78], and are probably associated with increases in vector abundance. Understanding how and when ENSO impacts malaria transmission in a speci c country and, more generally in a region like Mesoamerica, can be useful for preparing to timely deploy malaria control activities in Panamá.…”
Section: Association Between Malaria Incidence and Enso Eventsmentioning
confidence: 98%
“…Indeed, many migrants are from countries where drug resistant strains circulate, a fact that continuously challenges the national malaria program treatment policies [18]. In fact, recent P. falciparum outbreaks in areas where malaria transmission had been previously interrupted have been linked to migratory events across the Panamanian-Colombian border [9,[54][55][56]76]. During this period (2000-2019) a significant and increasing proportion of the P. falciparum total cases were imported, mainly from Colombia (Additional file 3 and 4).…”
Section: Climatic Factors and Malariamentioning
confidence: 99%